Dynamic Analysis of a Circular Tall Structure Considering Outriggers using ETABS A Review - Brijdeep Singh Bhatia; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
Deeply and outrigger underlying frameworks. Deeply and less powers are conveyed by the structure's fringe. This approach was likewise utilized for a structure of medium stature, notwithstanding tall designs. The objective of this study is to take a gander at the seismic variety in round structures by putting the Outrigger framework at the inward divider in the built up substantial design. In this review, we are presenting survey of past publications, journals and reference books
Keywords: Core And Outrigger Structural System; Connection Design; Dynamic Analysis; Time History; Rotational Seismic Analysis; Etabs